2006
DOI: 10.2337/db06-0733
|View full text |Cite
|
Sign up to set email alerts
|

Islet Microvasculature in Islet Hyperplasia and Failure in a Model of Type 2 Diabetes

Abstract: Gene expression profiling of islets from pre-diabetic male Zucker diabetic fatty (ZDF) rats showed increased expression of hypoxia-related genes, prompting investigation of the vascular integrity of the islets. The islet microvasculature was increased approximately twofold in young male ZDF rats by both morphometric analysis and quantifying mRNA levels of endothelial markers. ZDF rats at 12 weeks of age showed a significant reduction in the number of endothelial cells, which was prevented by pretreatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
137
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 57 publications
13
137
0
Order By: Relevance
“…Initially, the adaptive response of ␤ cells to insulin resistance involves both changes in mass and function that act to maintain normal glucose tolerance. In prediabetic ZDF rats, ␤-cell mass expansion is associated with the activation of certain hypoxia-inducible target genes (Li et al 2006). We also found that in ob/ob mice, which develop islet hyperplasia as a result of an adaptive response to spontaneous obesity due to leptin deficiency, certain HIF-target genes including Slc2a1, Pdk1, and Hif1␣ itself are activated (J. Zehetner and W. Krek, unpubl.).…”
Section: Pvhl-hif Regulates Insulin Secretion Genes and Development 3141mentioning
confidence: 78%
See 1 more Smart Citation
“…Initially, the adaptive response of ␤ cells to insulin resistance involves both changes in mass and function that act to maintain normal glucose tolerance. In prediabetic ZDF rats, ␤-cell mass expansion is associated with the activation of certain hypoxia-inducible target genes (Li et al 2006). We also found that in ob/ob mice, which develop islet hyperplasia as a result of an adaptive response to spontaneous obesity due to leptin deficiency, certain HIF-target genes including Slc2a1, Pdk1, and Hif1␣ itself are activated (J. Zehetner and W. Krek, unpubl.).…”
Section: Pvhl-hif Regulates Insulin Secretion Genes and Development 3141mentioning
confidence: 78%
“…In this regard, gene expression analysis of prediabetic and diabetic Zucker diabetic fatty (ZDF) rats, which carry a mutation in the leptin receptor gene and serve as a model for ␤-cell mass adaptation and decompensation during progression of type 2 diabetes, revealed that certain hypoxia-inducible target genes become activated at the prediabetic stage, coinciding with adaptive ␤-cell mass expansion (Li et al 2006). The hypoxia-inducible genes that are activated include those whose products influence glycolysis, such as lactate dehydrogenase A (LDHA) that catalyzes the conversion of pyruvate to lactate, as well as angiogenesis, such as vascular endothelial growth factor (VEGF) that is known to be critical for ␤-cell function (Lammert et al 2003).…”
mentioning
confidence: 99%
“…48,49 In addition, mice with GLUT2-deficient b-cells also have impaired insulin secretion, leading to diabetes development. 50 Therefore, defective glucose-sensing likely has a significant role in the impairment of b-cell function that is present in the VHL mutant mice. In addition to the changes observed within the VHL-deficient b-cells, there were significant alterations in islet architecture caused by increased vasculature likely due to Vegf upregulation, which may have influenced b-cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose stimulation of beta cell oxygen consumption generates intracellular hypoxia leading to activation of hypoxia-inducible factors (HIFs) and upregulation of HIF-target genes in rodent and human islets (reviewed in [1]). The presence of hypoxia in vivo in the islets of animal models of type 2 diabetes [3][4][5][6][7][8] supports a role for hypoxic stress in beta cell apoptosis. Moreover, severe hypoxia in islet grafts contributes to beta cell apoptosis in the early post-transplantation period [9,10].…”
Section: Introductionmentioning
confidence: 99%